Hispanic intermarriage in New York City : new evidence from 1991 - Gilbertson, G. a.; Fitzpatrick, J. P.; Yang, L.
tbls.
pp. 445-459
Keywords: Matrimonio; Inmigrantes; Latinoamericanos; Costumbres Matrimoniales; Estados Unidos de America